The effect of 12-weeks foot exercise on blood glucose levels, ankle brachial index, and sensation of protection in diabetes mellitus patients: A quasi-experiment study - Dewi, Rosliana; Budhiana, Johan; Agustina, Marina Pra; Melinda, Fera; Wahida, Astri Zeini (Faculty of Nursing Universitas Padjadjaran, 2024)
Background: Diabetes Mellitus (DM) is a global health issue causing nerve damage, blood vessel damage, and leg impairment. Foot exercises can improve risk factors for diabetic foot ulcers, neuropathy symptoms, pressure distribution, joint mobility, and strength in individuals with diabetes. Purpose: This study aimed to determine the effect of 12-weeks foot exercise on blood glucose levels, ABI values, and sensation of protection in diabetes mellitus patients West Java, Indonesia. Methods: The sample in this study was individuals aged 18 or above with a confirmed diagnosis of diabetes mellitus. A 154 patients willingly volunteered to participate and were subsequently enrolled in the study (77 in intervention group and 77 in control group). The study encompassed participants who engaged in a twelve-week regimen of foot exercises utilizing teaching modules and video materials.The study employed several tools, namely a glucometer, a glucometer stick, Ankle Brachial Index value, and a questionnaire. A bivariate analysis using the paired t-test and ANCOVA was conducted using IBM SPSS Statistics version 22.0. Results: In intervention group, random blood glucose was decreased significantly from 237.5 ± 9.56 at baseline to 188.0 ±6 9.19 after intervention (p=0.002). Sensation of protection as measure by the number of areas with loss sensation was improve from 5.21 ± 1.03 at baseline to 3.42 ± 1.21 after intervention (p=0.001). While, no significant improvement in ankle-brachial index after intervention (p=0.413). The ANCOVA test showed that between group, sensation of protection was significantly different in intervention group compare to control group (ß =0.413, p-value=0.038). Conclusions: The study found that a 12-week foot exercise program significantly improves blood glucose and sensation protection, but not ankle-brachial index. Further research is needed with a more rigorous study design and larger sample size.